Natural gas security evaluation from a supply vs. demand perspective: A quantitative application of four As. (September 2021) - Ye, Ruike; Zhou, Yunheng; Chen, Jiawei; Tu, Kevin
Abstract: The rising share of natural gas in global energy mix has resulted in concern over its security recently. But research from a perspective of exporting countries has not attracted enough attention. This study examines natural gas security from a supply vs. demand perspective. Firstly, a natural gas security index (NGSI) is formulated to quantify the NGSI score (NGSItot) of 22 selected countries, and the approach is based on a quantitative application of the "four As" of energy security. Secondly, a balance NGSI score (NGSIbla) matrix is introduced to gauge how well a specific country manages the trade-offs among the "four As". Key research findings are as follows: (1) Proven gas reserves per capita and Annual median PM2.5 concentration are more important than other indicators. (2) Nations that have a more balanced pattern against these four-A dimensions rank better. (3) According to the NGSIbla, eight countries fall into the Good group, ten in the Limited group, and four in the Weak group. Consequently, this study suggests that differentiated policy frameworks should be tailor-made for specific country to ensure natural gas security. This article contributes a replicable method of energy security evaluation, and a comprehensive policy framework to enhance natural gas security. Highlights: The composite index from a supply vs. demand perspective extends the application of "four As". A replicable two-step method of natural gas security evaluation is introduced. Nations that have a more balanced pattern against these 4-A dimensions rank better. According to the NGSIbla, eight countries fall into the Good group, ten in the Limited group, and four in the Weak group. An appropriate policy framework must balance between increasing gas supply and stable demand.